Scalp involvement in pemphigus - Sar-Pomian, Marta; Kołacińska-Strasz, Zofia; Łabęcka, Hanna; Kraińska-Wójcik, Teresa; Olszewska, Małgorzata (Dermatology Review/Przegląd Dermatologiczny, 2010)
Introduction. Pemphigus is an autoimmune disorder characterized by intra-epidermal blister formation. Objective. We studied the clinical and immunological profile of pemphigus patients with scalp involvement. Material and methods. Six patients (4 with pemphigus vulgaris and 2 with pemphigus foliaceus) with pemphigus-specific lesions on the scalp were included in the study. Direct immunofluorescence test of scalp biopsy was performed and pemphigus antibodies were evaluated with indirect immunofluorescence and enzyme-linked immunosorbent assay. Clinical course of the disease was assessed. Results. We found IgG and C3 deposits in hair follicles and surround-ing epidermis in all patients with active lesions on the scalp. Indirect immunofluorescence demonstrated pemphigus antibodies in titres of 640-1280 and 160-1280 on monkey and guinea pig oesophagus respectively in patients with pemphigus vulgaris. In patients with pemphigus foliaceus the titres were 320-1280 and 320-1280 respectively. Enzyme-linked immunosorbent assay showed anti-Dsg3 and anti-Dsg1 antibodies in patients with pemphigus vulgaris and anti-Dsg1 antibodies in patients with pemphigus foliaceus. Three of 6 patients had chronic, recalcitrant disease with relapses. All patients, in the past or at the time of the study, underwent combined treatment with steroids and adjuvant drugs. Conclusions. Scalp involvement in pemphigus vulgaris and foliaceus can be a bad prognostic factor, pointing to possible chronic and recalcitrant disease with relapses.